Sustained Inflammasome Activity in Macrophages Impairs Wound Healing in Type 2 Diabetic Humans and Mice - Mirza, Rita E.; Fang, Milie M.; Weinheimer-Haus, Eileen M.; Ennis, William J.; Koh, Timothy J. (Diabetes (New York, N.Y.), 2014)
The hypothesis of this study was that sustained activity of the Nod-like receptor protein (NLRP)-3 inflammasome in wounds of diabetic humans and mice contributes to the persistent inflammatory response and impaired healing characteristic of these wounds. Macrophages (Mp) isolated from wounds on diabetic humans and db/db mice exhibited sustained inflammasome activity associated with low level of expression of endogenous inflammasome inhibitors. Soluble factors in the biochemical milieu of these wounds are sufficient to activate the inflammasome, as wound-conditioned medium activates caspase-1 and induces release of interleukin (IL)-1β and IL-18 in cultured Mp via a reactive oxygen species–mediated pathway. Importantly, inhibiting inflammasome activity in wounds of db/db mice using topical application of pharmacological inhibitors improved healing of these wounds, induced a switch from proinflammatory to healing-associated Mp phenotypes, and increased levels of prohealing growth factors. Furthermore, data generated from bone marrow–transfer experiments from NLRP-3 or caspase-1 knockout to db/db mice indicated that blocking inflammasome activity in bone marrow cells is sufficient to improve healing. Our findings indicate that sustained inflammasome activity in wound Mp contributes to impaired early healing responses of diabetic wounds and that the inflammasome may represent a new therapeutic target for improving healing in diabetic individuals.